2009
DOI: 10.1124/dmd.108.024711
|View full text |Cite
|
Sign up to set email alerts
|

Two Nonsynonymous Single Nucleotide Polymorphisms of Human Carbonyl Reductase 1 Demonstrate Reduced in Vitro Metabolism of Daunorubicin and Doxorubicin

Abstract: ABSTRACT:Carbonyl reductases (CBRs) are a group of metabolic enzymes belonging to the short-chain dehydrogenase family with NADPHdependent oxidoreductase activity. These enzymes are known to metabolize the anthracyclines doxorubicin (DOX) and daunorubicin (DAUN). Both DOX and DAUN are highly effective in cancer therapy; however, there is considerable interpatient variability in adverse effects seen in patients undergoing treatment with these drugs. This may be attributed to altered metabolism associated with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
42
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 32 publications
3
42
0
2
Order By: Relevance
“…Recently, we found that resveratrol inhibits enzymatic activity of carbonyl reductase 1 (CBR1), a doxorubicin-metabolizing enzyme, by directly binding to CBR1 (14). CBR1 is an NADPH-dependent enzyme belonging to the short chain dehydrogenase family and catalyzes a large number of biologically and pharmacologically active substrates, including endogenous substrates such as prostaglandin E2 and S-nitrosogluthathione and xenobiotic substrates such as anthracycline anti- cancer drugs (doxorubicin and daunorubicin) (15)(16)(17). Since doxorubicin causes DNA damage by intercalating itself into the DNA base pairs of the double helix, it is used for the treatment of broad range of solid tumors, including breast cancer and hepatocellular carcinoma cells (18,19).…”
mentioning
confidence: 99%
“…Recently, we found that resveratrol inhibits enzymatic activity of carbonyl reductase 1 (CBR1), a doxorubicin-metabolizing enzyme, by directly binding to CBR1 (14). CBR1 is an NADPH-dependent enzyme belonging to the short chain dehydrogenase family and catalyzes a large number of biologically and pharmacologically active substrates, including endogenous substrates such as prostaglandin E2 and S-nitrosogluthathione and xenobiotic substrates such as anthracycline anti- cancer drugs (doxorubicin and daunorubicin) (15)(16)(17). Since doxorubicin causes DNA damage by intercalating itself into the DNA base pairs of the double helix, it is used for the treatment of broad range of solid tumors, including breast cancer and hepatocellular carcinoma cells (18,19).…”
mentioning
confidence: 99%
“…Lars P. Jordheim, 1,2,3 Vincent Ribrag, 4 Hervé Ghesquieres, 5 Sophie Pallardy, 6 Richard Delarue, 7 Hervé Tilly,8 Corinne Haioun, 9 Fabrice Jardin, 10 Delphine Demangel, 2,3 Gilles A. Salles 11 …”
unclassified
“…7 CBR1 has also been suspected to be involved in the occurrence of anthracycline-related toxicities as non-synonymous SNP were associated with reduced metabolism of doxorubicin and daunorubicin, and as these metabolisms were correlated to the expression of carbonyl reductases. 8,9 In addition, polymorphisms in CBR1 were correlated with altered pharmacokinetics with increased exposure to doxorubicin. 10 Finally, the cardioprotectant flavonoid 7-monohydroxyethyl rutoside was shown to behave as a CBR1 inhibitor.…”
mentioning
confidence: 99%
“…CBR1 is also hypothesized to participate in cellular processes such as signal transduction (7), apoptosis (8), carcinogenesis (9) and drug resistance (10), and serves an important role in endometrial cancer (11), acute myeloid leukemia (12) and hepatocellular carcinoma (13). Schlager and Powis (14) reported that the level of CBR1 activity was significantly increased in lung tumors compared within normal tissue.…”
Section: Introductionmentioning
confidence: 99%